GIS-material for the archaeological project: 3G tower in Uljeberg - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the planned construction of a 3G tower and a connection road within the property Uljeberg 8:2, Viby parish, Mjölby municipality, the Swedish National Heritage Board's contract arcaheology division, UV Öst, has performed a preliminary investigation in May 2005. The 3G tower was to be constructed within the protected area of a burial ground and on a potential settlement location. No finds or features were found.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine whether the protected area of archaeological site RAÄ 25 extended into the development area. The aim of the investigation was also to examine if there were any unmarked archaeological remains within the development area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har i maj 2005 genomfört en arkeologisk förundersökning inför ett planerat 3G-torn och anslutande väg på fastigheten Uljeberg 8:2 i Viby socken, Mjölby kommun. 3G-tornet skulle uppföras inom fornlämningsområdet tillhörande ett gravfält, på en plats som även är ett lämpligt boplatsläge. Inga fynd eller anläggningar påträffades.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen var att avgöra om fornlämningsområdet till RAÄ 25 sträckte sig in i exploateringsområdet. Förundersökningen skulle även ta reda på om det fanns andra fornlämningar som inte syns ovan mark inom exploateringsområdet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: 3G torn i Uljeberg
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi